A Corpus-Based Study of Pronouns in Bahasa Indonesia: A Case Study of Aku/Saya and Kita/Kami - Eva Tuckyta Sari Sujatna; Kasno Pamungkas; Meita Lukitawati Sujatna (SAWERIGADING, 2024)
The first-person pronouns in Bahasa Indonesia have two forms: singular and plural. The singular pronoun forms are saya and aku for the singular pronoun forms, while the plural pronoun forms for the first-person are kita and kami. This paper aims to figure out the highest number of both singular and plural forms in Bahasa Indonesia, the number of the first-person singular pronouns form aku and saya, and the number of the plural pronouns for first-person forms kami and kita. The corpus linguistic method is applied in this research. Using corpus software, vis. AntConc 3.5.8 tool, the pronouns aku, saya, kita, and kami were identified. The 8,432,978 tokens were obtained from four different sources: newspapers, magazines, short stories, and novels. From the number of collected tokens, 224,796 corpora were classified as singular and plural pronouns. The result of the research shows that 1) the amount of the singular pronoun for the first-person is higher than the plural form; 2) the quantity of the singular pronoun form for the first-person aku is higher than saya; and 3) the usage of the plural pronoun of the first-person forms kami is higher than kita established in the four sources of the corpus.  AbstrakPronomina orang pertama di dalam bahasa Indonesia memiliki dua bentuk: tunggal dan jamak. Bentuk pronomina tunggal adalah saya dan aku, sedangkan bentuk jamaknya adalah kita dan kami. Tujuan penelitian ini mendeskripsikan pronomina yang memiliki jumlah terbanyak yang berbentuk tunggal dan jamak dalam bahasa Indonesia, baik pronomina orang pertama berbentuk tunggal saya dan aku serta pronomina orang pertama yang berbentuk jamak kami dan kita. Penelitian ini menggunakan metode linguistik korpus. Dengan menggunakan perangkat lunak korpus, vis. aplikasi AntConc 3.5.8, kata ganti aku, saya, kita, dan kami diidentifikasi. Sebanyak 8.432.978 token yang berasal dari koran, majalah, cerita pendek, dan novel digunakan sebagai data penelitian ini. Dari sejumlah token tersebut, 224.796 korpus diklasifikasikan. Hasil penelitian menunjukkan bahwa 1) jumlah pronomina orang pertama tunggal lebih banyak dari pronomina orang pertama jamak; 2) penggunaan pronomina aku lebih banyak dari saya; dan 3) dari empat sumber korpus yang digunakan dilaporkan bahwa penggunaan pronomina orang pertama jamak kami lebih banyak dari kita.